PENGARUH PELAYANAN PEMANDU WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI MUSEUM SULTAN MAHMUD BADARUDIN II KOTA PALEMBANG - Dian Anggola; Esya Alhadi; Hadi Jauhari (Politeknik Negeri Sriwijaya, 2020)
This study aims to determine the effect of tour guide services on visiting decisions at the Sultan Mahmud Badarudin II Museum in Palembang. The research data uses secondary data and primary data. Secondary research data were obtained from the Palembang City Culture Office. The number of samples was 60 respondents (non probability sampling method with purposive sampling technique). Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Based on the results of research simultaneously Professional Competence, Interpersonal Skill, Organization Skill, Emphaty and Problem Solving tour guides have a positive effect on visiting decisions. While partially it shows that 1 variable meets the requirements for acceptance of the hypothesis and 4 other variables have no positive influence or Ho is rejected. From the determination results, it is found that the tour guide service on visiting decisions has an effect of 66.2% on the visiting decision. The rest is explained by other independent variables not examined in this study. Suggestions given to improve the quality of tour guide services are to improve current topics, speak clearly, provide timely services, offer assistance to tourists, actively listen and are dexterous in resolving conflicts.